Climate Change Analysis (Monthly Rainfall) on Palembang Duku Production (Lansium domesticum Corr) - Ratih Wijayanti; Edward Saleh; Herlina Hanum; Nabila Aprianti (Program Pascasarjana Universitas Sriwijaya, 2020)
Climate is one of the conditions needed by plants to increase production. Climate change, especially on rainfall has a significant effect on agriculture because it has a strong dependence on the climate element. Rainfall is one of the climate factors that play a role in supporting the availability of water. Conditions in areas with high rainfall intensity can cause the loss of flowers and fruit, and if there is a long dry season it will affect flowering on plants. This study aimed to determine the effect of rainfall on L. domesticum production for 10 years (2010-2019). The study was conducted in OKU and OKI Regencies. The analytical method used is multiple linear analysis and correlation analysis. From multiple linear analysis and correlation analysis results, there was a fluctuation in the intensity of rainfall for 10 years (2010-2019). Based on the regression analysis, rainfall in June for OKU Regency had a significant effect on L. domesticum production while for OKI Regency the significance occurred in December.